Analisis Perubahan Rasio Profitabilitas Sebelum dan Pada Masa Pandemi Covid 19 dan Hubungannya Terhadap Pertumbuhan Laba - Angrawit Kusumawardani (Forum Kerjasama Pendidikan Tinggi, 2022)
Performing an analysis is very important for an investor and the company itself to find out what are the important points in increasing profit growth. The COVID-19 pandemic conditions have forced banks to make effective and efficient strategies so that banks remain in a stable condition with limited social restrictions imposed by the government. In this study, the authors analyze changes in profitability ratios before and during the COVID-19 pandemic and their relationship to profit growth. The object of this research is the quarterly financial statements of state-owned banks 2018-2021. The result is that simultaneously profitability affects profit growth, while partially ROA, ROE, and BOPO ratios affect profit growth but the NIM ratio has no significant effect on profit growth.